The Effect of Firm Size and Financial Distress on Going Concern Audit Opinion - Muhammad Arya Lokamandala; Poppy Sofia Koeswayo; Devianti Yunita Harahap (Journal of Accounting Auditing and Business, 2023)
This study aims to analyze the effect of firm size and financial distress on the reception of the going concern audit opinion in the Accommodation and Food and Beverages Sub-Sector listed in the Indonesian Stock Exchange between 2019 and 2021. This study employed the quantitative approach and the methods of descriptive and verification analysis. The data analyzed in this study came from secondary sources. The data were analyzed using descriptive and logistic regression analysis. These analyses show that firm size and financial distress do not significantly impact the going concern audit opinion in the Accommodation and Food and Beverages sector between 2019 and 2021. These variables only contribute 5.8% to the reception of the going concern audit opinion.